Swallowed topical corticosteroids reduce the risk for long‐lasting bolus impactions in eosinophilic esophagitis. Issue 9 (3rd July 2014) - Kuchen, T.; Straumann, A.; Safroneeva, E.; Romero, Y.; Bussmann, C.; Vavricka, S.; Netzer, P.; Reinhard, A.; Portmann, S.; Schoepfer, A. M.
Abstract Background Long‐lasting food impactions requiring endoscopic bolus removal occur frequently in patients with eosinophilic esophagitis (EoE) and harbor a risk for severe esophageal injuries. We evaluated whether treatment with swallowed topical corticosteroids is able to reduce the risk of occurrence of this complication. Methods We analyzed data from the Swiss EoE Cohort Study. Patients with yearly clinic visits, during which standardized assessment of symptoms, endoscopic, histologic, and laboratory findings was carried out, were included. Results A total of 206 patients (157 males) were analyzed. The median follow‐up time was 5 years with a total of 703 visits (mean 3.41 visits/patient). During the follow‐up period, 33 patients (16 % of the cohort) experienced 42 impactions requiring endoscopic bolus removal. We evaluated the following factors regarding the outcome 'bolus impaction' by univariate logistic regression modeling: swallowed topical corticosteroid therapy (OR 0.503, 95%‐CI 0.255–0.993, P = 0.048), presence of EoE symptoms (OR 1.150, 95%‐CI 0.4668–2.835, P = 0.761), esophageal stricture (OR 2.832, 95%‐CI 1.508–5.321, P = 0.001), peak eosinophil count >10 eosinophils/HPF (OR 0.724, 95%‐CI 0.324–1.621, P = 0.433), blood eosinophilia (OR 1.532, 95%‐CI 0.569–4.118, P = 0.398), and esophageal dilation (OR 1.852, 95%‐CI 1.034–3.755, P = 0.017). In the multivariate model, the following factors were significantly associated with bolus impaction: swallowed topical corticosteroid therapy (OR 0.411, 95%‐CI 0.203–0.835, P = 0.014) and esophageal stricture (OR 2.666, 95%‐CI 1.259–5.645, P = 0.01). Increasing frequency of use of swallowed topical steroids was associated with a lower risk for bolus impactions. Conclusions Treatment of EoE with swallowed topical corticosteroids significantly reduces the risk for long‐lasting bolus impactions.